China's economic development: decoding and reframing its rise - Lee, Pei May (Routledge, Taylor & Francis Group, 2024)
Through a rigorous examination of “China’s rise”, Lee addresses an important question—Did China catch up? Or more specifically, can growth be automatically translated to catching up with the advanced industrialised countries or has it only allowed limited progress (if any) to be made?